Wind power generation cable and preparation method thereof
By applying modified coniferous wood fiber and nano-magnesium oxide and other materials, the problem of insufficient mechanical properties and electrical insulation properties of wind power cables has been solved, the tensile strength, electrical insulation properties and heat resistance of the cables have been improved, and the service life has been extended.
Patent Information
- Application Number
- CN202510793231.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-13
- Publication Date
- 2025-10-10
AI Technical Summary
Existing wind power cables are insufficient in mechanical properties, electrical insulation properties and aging resistance, and are prone to fatigue accumulation and damage, especially in harsh environments.
By using materials such as hyperbranched grafted modified coniferous wood fiber, modified nano-magnesium oxide and specific cross-linking agents, and optimizing the composition and preparation process of the insulation layer, the tensile strength, electrical insulation performance and heat resistance of the cable are improved.
It significantly enhances the mechanical properties and electrical insulation properties of wind power cables, prolongs their service life, and improves their stability and reliability in high voltage and high temperature environments.
Smart Images

Figure SMS_1 
Figure SMS_4 
Figure SMS_5
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of cable materials, in particular to a wind power cable and a preparation method thereof. BACKGROUND
[0002] The wind power cable is a power transmission cable specially used in a wind power system. Since the wind power system is usually installed in a harsh natural environment, such as offshore and high mountains, the cable has high requirements for performance. The main structure of the wind power cable includes a conductor, an insulation layer and a protective sleeve. The selection and performance of the insulation layer material play an important role in the overall performance of the cable.
[0003] In the wind power system, the cable needs to withstand a large mechanical stress. In particular, when the wind changes greatly, the insufficient tensile strength of the cable can cause the cable to break or be damaged. In addition, the blades of the wind turbine generate a torsional force during rotation. The cable needs to have good anti-torsion performance. The existing cable is prone to fatigue accumulation under the action of repeated torsion and mechanical stress, resulting in a decrease in material performance. The wind power cable needs to have high breakdown strength when working in a high voltage environment. The wind power system generates a large amount of heat during operation. The cable needs to have good heat resistance and anti-aging ability.
[0004] Therefore, according to the related technology in the above, it is urgent to develop a wind power cable and a preparation method thereof. SUMMARY
[0005] In view of this, the purpose of the present application is to provide a high-performance wind power cable and a preparation method thereof to solve the problems of insufficient mechanical performance, electrical insulation performance and anti-aging performance of the wind power cable in the prior art.
[0006] To achieve the above purpose, the present application adopts the following technical solutions:
[0007] In a first aspect, the present application provides a wind power cable, which is composed of a conductor, an insulation layer and a protective sleeve arranged from inside to outside.
[0008] The insulation layer material is made of the following raw materials by mass: low-density polyethylene 50-60 parts, ethylene-methyl acrylate copolymer 10-15 parts, hyperbranched grafting modified coniferous wood fiber 5-10 parts, modified nano magnesium oxide 2-4 parts, crosslinking agent 6-8 parts, peroxide 2-3 parts and crosslinking agent auxiliary agent 0.5-1 part.
[0009] Preferably, the density of the low-density polyethylene is 0.910-0.940 g / cm 3 , and the molecular weight distribution (Mw / Mn) of the low-density polyethylene is 3.0-5.0.
[0010] Preferably, the preparation method of the hyperbranched graft modified coniferous wood fiber:
[0011] Step A1: coniferous wood fiber is soaked in 3-aminopropyl triethoxysilane aqueous solution for 3-5 h, the solid-liquid ratio of coniferous wood fiber and 3-aminopropyl triethoxysilane aqueous solution is 1:6-8, after washing and drying, silanized coniferous wood fiber is obtained, the silanized coniferous wood fiber is dispersed in anhydrous methanol a1, methyl acrylate a and triethylamine a are added, 60-65℃, N2 protection, reaction for 5-6 h, after washing and drying, anhydrous methanol a2 and ethylenediamine a are added, 55-60℃, N2 protection, reaction for 7-8 h, to obtain modified coniferous wood fiber A;
[0012] Step A2: the modified coniferous wood fiber A is dispersed in anhydrous methanol b1, methyl acrylate b and triethylamine b are added, 65-70℃, N2 protection, reaction for 5-6 h, after washing and drying, anhydrous methanol b2 and ethylenediamine b are added, 55-60℃, N2 protection, reaction for 7-8 h, to obtain modified coniferous wood fiber B;
[0013] Step A3: the modified coniferous wood fiber B is dispersed in anhydrous methanol c1, hydroxyethyl acrylate and triethylamine c are added, 65-70℃, N2 protection, reaction for 5-6 h, after washing and drying, anhydrous methanol c2 and ethylenediamine c are added, 55-60℃, N2 protection, reaction for 7-8 h, to obtain hyperbranched graft modified coniferous wood fiber.
[0014] The hyperbranched graft modified coniferous wood fiber is grafted and modified on the surface of the coniferous wood fiber with hyperbranched polyamide, a large number of active amino groups and hydroxyl groups are introduced, which are easy to form hydrogen bonds or covalent bonds with polar groups in insulating layer materials such as polyethylene, low-density polyethylene, ethylene-methyl acrylate copolymer, modified nano magnesium oxide and other materials, thereby improving the interfacial bonding force of the fiber and other materials, and the mechanical properties of the insulating layer material. To some extent, the hyperbranched structure can play a heat shielding role, delaying the transfer and accumulation of heat, and secondly, the amino groups in the hyperbranched structure can capture free radicals at high temperatures, inhibit the thermal oxidative degradation of the insulating layer material, and prolong the service life of the insulating layer material.
[0015] Preferably, the mass ratio of the coniferous wood fiber, 3-aminopropyl triethoxysilane aqueous solution, methyl acrylate a, methyl acrylate b, hydroxyethyl acrylate, triethylamine a, triethylamine b, triethylamine c, ethylenediamine a, ethylenediamine b, ethylenediamine c is 10:60-80:0.85-1.3:1.7-2.6:3.5-5.5:1.05-1.4:2.1-2.8:4.2-5.6:0.6-1.05:1.2-2.1:2.4-4.2.
[0016] Preferably, the mass fraction of the 3-aminopropyltriethoxysilane aqueous solution is 8%-10%, and the pH value of the 3-aminopropyltriethoxysilane aqueous solution is 5-6.
[0017] Preferably, the solid-liquid ratio of the coniferous wood fiber and anhydrous methanol a1 is 1:10, and the volume ratio of anhydrous methanol a1, anhydrous methanol a2, anhydrous methanol b1, anhydrous methanol b2, anhydrous methanol c1 and anhydrous methanol c2 is 1:1:2:2:4:4.
[0018] The methyl acrylate a and methyl acrylate b both refer to the same methyl acrylate.
[0019] The triethylamine a, triethylamine b, and triethylamine c all refer to the same triethylamine.
[0020] The ethylenediamine a, ethylenediamine b, and ethylenediamine c all refer to the same ethylenediamine.
[0021] The anhydrous methanol a1, anhydrous methanol a2, anhydrous methanol b1, anhydrous methanol b2, and anhydrous methanol c1 refer to the same type of anhydrous methanol.
[0022] Preferably, the preparation method of the modified nano-magnesium oxide is as follows: nano-magnesium oxide powder is ultrasonically dispersed in 3-aminopropyltriethoxysilane isopropanol solution, the solid-liquid ratio of nano-magnesium oxide powder and 3-aminopropyltriethoxysilane isopropanol solution is 1:5, stirring at 65°C-75°C for 8-10 hours, filtering and drying to obtain modified nano-magnesium oxide.
[0023] Preferably, the volume ratio of 3-aminopropyltriethoxysilane to isopropanol in the 3-aminopropyltriethoxysilane isopropanol solution is 1:10.
[0024] Preferably, the preparation method of the cross-linking agent is: mixing glycidyl methacrylate and isooctyl acrylate, adding azobisisobutyronitrile and n-dodecyl mercaptan, reacting at 80°C-90°C under N2 protection for 7-8h, extracting, drying and purifying to obtain a glycidyl methacrylate-isooctyl acrylate binary polymer, i.e., the cross-linking agent.
[0025] The glycidyl methacrylate-isooctyl acrylate binary polymer introduces isooctyl acrylate with longer alkyl side chains. These side chains provide more free volume and segment mobility in the polymer chain, thereby improving the flexibility and impact resistance of the copolymer and reducing the brittleness of the material.
[0026] Preferably, the mass ratio of glycidyl methacrylate, isooctyl acrylate, azobisisobutyronitrile and n-dodecyl mercaptan is 10:30-35:1-1.5:4-4.5.
[0027] Preferably, the peroxide is any one or both of di-tert-butyl peroxide isopropylbenzene, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane.
[0028] Preferably, the crosslinking agent auxiliary is any one or both of triallyl isocyanurate, trimethylolpropane triacrylate.
[0029] Preferably, the preparation method of the insulating layer material is as follows: low-density polyethylene, ethylene-methyl acrylate copolymer, hyperbranched graft-modified coniferous wood fiber, modified nano-magnesium oxide, crosslinking agent, crosslinking agent auxiliary, and antioxidant are uniformly mixed at 120-130 DEG C in a torque rheometer to obtain a mixed sample, the mixed sample is placed in a flat plate vulcanizing machine and hot-pressed at 120-130 DEG C and 15 MPa for 10-15 min, and then crosslinked at 180-190 DEG C and 15 MPa for 30-40 min to obtain the insulating layer material.
[0030] In a second aspect, the present application provides a preparation method of the wind power cable, which comprises sequentially coating an insulating layer and a protective sleeve on the outer surface of the conductor to obtain the high-performance wind power cable.
[0031] The present application has the following advantages:
[0032] 1. The insulating layer is prepared by using specific materials such as hyperbranched graft-modified coniferous wood fiber and processes, so that the mechanical properties such as tensile strength and elongation at break of the wind power cable are significantly enhanced, the wind power cable can better withstand the large mechanical stress in the wind power system, the risk of fracture or damage of the cable due to mechanical stress in the use process is effectively reduced, and the reliability and service life of the cable are improved.
[0033] 2. The surface of the nano-magnesium oxide is modified to introduce amino and siloxane functional groups on the surface, these functional groups can act as deep trap centers to effectively capture carriers, thereby inhibiting the accumulation of space charges, and further improving the electrical insulation performance of the insulating layer material, so that the cable has higher safety and stability when working in a high-voltage environment, and the risk of electrical breakdown is reduced.
[0034] 3. The hyperbranched structure of the hyperbranched graft-modified coniferous wood fiber can play a heat shielding role to a certain extent, delaying the transfer and accumulation of heat, and its amino groups can capture free radicals at high temperatures to inhibit the thermal oxidative degradation of the insulating layer material; in addition, by reasonably selecting materials such as crosslinking agents and crosslinking agent auxiliaries and optimizing the preparation process, the heat resistance and anti-aging ability of the insulating layer material are further improved, so that the cable can work stably for a long time in the high-temperature environment generated during the operation of the wind power system, and the service life of the cable is prolonged.
[0035] 4. The introduction of glycidyl methacrylate-hexyl acrylate binary polymer, which has long alkyl side chains in its structure, these side chains provide more free volume and segment motion ability in the polymer chain, improve the flexibility and impact resistance of the copolymer, so that the composite material can better disperse stress under the action of repeated twisting and mechanical stress, reduce the fatigue accumulation of the material, thereby significantly improve the twisting resistance of the wind power cable and ensure the performance stability of the cable under complex working conditions. DETAILED DESCRIPTION
[0036] In order to make the objects, technical solutions and advantages of the present application clearer, the present application will be further described in detail below with specific examples.
[0037] Example 1:
[0038] A preparation method of a wind power cable, comprising the following steps:
[0039] S1: 5g of coniferous wood fibers are soaked in 30mL of 3-aminopropyl triethoxysilane aqueous solution with a mass fraction of 8% and a pH of 5 for 3h, washed and dried, and then dried to obtain silanized coniferous wood fibers. The silanized coniferous wood fibers are dispersed in 50mL of anhydrous methanol a1, 0.85g of methyl acrylate a and 1.05g of triethylamine a are added, and the reaction is carried out at 60℃ under N2 protection for 5h. After washing and drying, 50mL of anhydrous methanol a2 and 0.6g of ethylenediamine a are added, and the reaction is carried out at 55℃ under N2 protection for 7h to obtain modified fibers A;
[0040] S2: The modified coniferous wood fibers A are dispersed in 100mL of anhydrous methanol b1, 1.7g of methyl acrylate b and 2.1g of triethylamine b are added, and the reaction is carried out at 65℃ under N2 protection for 5h. After washing and drying, 100mL of anhydrous methanol b2 and 1.2g of ethylenediamine b are added, and the reaction is carried out at 55℃ under N2 protection for 7h to obtain modified coniferous wood fibers B;
[0041] S3: The modified coniferous wood fibers B are dispersed in 200mL of anhydrous methanol c1, 3.5g of hydroxyethyl acrylate and 4.2g of triethylamine c are added, and the reaction is carried out at 65℃ under N2 protection for 5h. After washing and drying, 200mL of anhydrous methanol c2 and 2.4g of ethylenediamine c are added, and the reaction is carried out at 55℃ under N2 protection for 7h to obtain hyperbranched grafted modified coniferous wood fibers;
[0042] S4: 2g of nano magnesium oxide powder is ultrasonically dispersed in 10mL of 3-aminopropyl triethoxysilane isopropyl alcohol solution, the volume ratio of 3-aminopropyl triethoxysilane to isopropyl alcohol in the 3-aminopropyl triethoxysilane isopropyl alcohol solution is 1:10, and the reaction is carried out at 65℃ under stirring for 10h. After filtration and drying, modified nano magnesium oxide is obtained;
[0043] S5: 2 g of glycidyl methacrylate and 6 g of isooctyl acrylate were mixed, 0.2 g of azobis isobutyronitrile and 0.8 g of n-dodecanethiol were added, and the reaction was carried out at 80°C for 7 h under N2 protection. After extraction, drying and purification, a glycidyl methacrylate-isooctyl acrylate binary polymer was obtained;
[0044] S6: 50 g of low-density polyethylene, 10 g of ethylene-methyl acrylate copolymer, 11.5 g of hyperbranched grafted modified coniferous wood fiber, 2 g of modified nano magnesium oxide, 6 g of glycidyl methacrylate-isooctyl acrylate binary polymer, 2 g of bis-tert-butyl peroxyisopropylbenzene, and 0.5 g of triallyl isocyanurate were uniformly mixed in a torque rheometer at 120°C to obtain a mixed sample. The mixed sample was placed in a flat plate vulcanizing machine and hot-pressed at 120°C and 15 MPa for 15 min. The temperature was raised to 180°C, and crosslinking was carried out at 15 MPa for 40 min to obtain an insulating layer material;
[0045] S7: After the copper core conductor was coated with the insulating layer material, a polyurethane protective sleeve was extruded and coated on the outer layer to obtain a wind power cable.
[0046] Example 2:
[0047] A method for preparing a wind power cable, comprising the following steps:
[0048] S1: 5 g of coniferous wood fiber was soaked in 35 mL of 3-aminopropyl triethoxysilane aqueous solution with a mass fraction of 9% and a pH of 5.5 for 4 h. After washing and drying, the silanized coniferous wood fiber was obtained. The silanized coniferous wood fiber was dispersed in 50 mL of anhydrous methanol a1, 1.1 g of methyl acrylate a and 1.2 g of triethylamine a were added, and the reaction was carried out at 63°C under N2 protection for 5 h. After washing and drying, 50 mL of anhydrous methanol a2 and 0.8 g of ethylenediamine a were added, and the reaction was carried out at 58°C under N2 protection for 7 h to obtain modified fiber A;
[0049] S2: The modified coniferous wood fiber A was dispersed in 100 mL of anhydrous methanol b1, 2.2 g of methyl acrylate b and 2.4 g of triethylamine b were added, and the reaction was carried out at 68°C under N2 protection for 5.5 h. After washing and drying, 100 mL of anhydrous methanol b2 and 1.6 g of ethylenediamine b were added, and the reaction was carried out at 57°C under N2 protection for 8 h to obtain modified coniferous wood fiber B;
[0050] S3: The modified coniferous wood fiber B was dispersed in 200 mL of anhydrous methanol c1, 4.3 g of hydroxyethyl acrylate and 4.8 g of triethylamine c were added, and the reaction was carried out at 68°C under N2 protection for 5.5 h. After washing and drying, 200 mL of anhydrous methanol c2 and 3.2 g of ethylenediamine c were added, and the reaction was carried out at 58°C under N2 protection for 7.5 h to obtain hyperbranched grafted modified coniferous wood fiber;
[0051] S4: 3 g of nano-magnesium oxide powder was ultrasonically dispersed in 15 mL of 3-aminopropyl triethoxysilane isopropanol solution, the volume ratio of 3-aminopropyl triethoxysilane and isopropanol in the 3-aminopropyl triethoxysilane isopropanol solution was 1:10, stirring at 70°C for 9 h, filtering and drying to obtain modified nano-magnesium oxide;
[0052] S5: 2.5 g of glycidyl methacrylate and 8 g of isooctyl acrylate were mixed, 0.3 g of azobis isobutyronitrile and 1.05 g of n-dodecanethiol were added, and the mixture was reacted at 80°C under N2 protection for 7 h, and then extracted, dried and purified to obtain a glycidyl methacrylate-isooctyl acrylate binary polymer;
[0053] S6: 55 g of low-density polyethylene, 12 g of ethylene-methyl acrylate copolymer, 13.5 g of hyperbranched grafted modified coniferous wood fiber, 4 g of modified nano-magnesium oxide, 10.5 g of glycidyl methacrylate-isooctyl acrylate binary polymer, 2.5 g of 2,5-dimethyl-2,5-di(tert-butyl peroxy), and 1.0 g of trimethylolpropane triacrylate were mixed uniformly in a torque rheometer at 125°C to obtain a mixed sample, the mixed sample was placed in a flat plate vulcanizing machine and hot pressed at 120°C and 15 MPa for 12 min, and then crosslinked at 185°C and 15 MPa for 35 min to obtain an insulating layer material;
[0054] S7: After the copper core conductor was coated with the insulating layer material, a polyurethane protective sleeve was extruded and coated on the outer layer to obtain a wind power cable.
[0055] Example 3:
[0056] A method for preparing a wind power cable, comprising the following steps:
[0057] S1: 5 g of coniferous wood fiber was soaked in 40 mL of 3-aminopropyl triethoxysilane aqueous solution with a mass fraction of 10% and a pH of 6 for 5 h, and then washed and dried to obtain silanized coniferous wood fiber, which was dispersed in 50 mL of anhydrous methanol a1, 1.3 g of methyl acrylate a and 1.4 g of triethylamine a were added, and the mixture was reacted at 60°C under N2 protection for 6 h, and then washed and dried, 50 mL of anhydrous methanol a2 and 1.05 g of ethylenediamine a were added, and the mixture was reacted at 60°C under N2 protection for 8 h to obtain modified fiber A;
[0058] S2: The modified coniferous wood fiber A was dispersed in 100 mL of anhydrous methanol b1, 2.6 g of methyl acrylate b and 2.8 g of triethylamine b were added, and the mixture was reacted at 70°C under N2 protection for 6 h, and then washed and dried, 100 mL of anhydrous methanol b2 and 2.1 g of ethylenediamine b were added, and the mixture was reacted at 60°C under N2 protection for 8 h to obtain modified coniferous wood fiber B;
[0059] S3: dispersing the modified coniferous wood fiber B in 200 mL of anhydrous methanol c1, adding 5.5 g of hydroxyethyl acrylate and 5.6 g of triethylamine c, and reacting at 70°C under N2 protection for 6 h, and after washing and drying, adding 200 mL of anhydrous methanol c2 and 4.2 g of ethylenediamine c, and reacting at 60°C under N2 protection for 8 h to obtain a hyperbranched grafted modified coniferous wood fiber;
[0060] S4: ultrasonic dispersion of 4 g of nano magnesium oxide powder in 20 mL of a 3- aminopropyl triethoxysilane isopropyl alcohol solution, the volume ratio of 3- aminopropyl triethoxysilane to isopropyl alcohol in the 3-aminopropyl triethoxysilane isopropyl alcohol solution being 1:10, stirring at 70°C for 8 h, and filtering and drying to obtain modified nano magnesium oxide;
[0061] S5: mixing 3 g of glycidyl methacrylate and 10.5 g of isooctyl acrylate, adding 0.45 g of azobis isobutyronitrile and 1.35 g of n-dodecanethiol, and reacting at 90°C under N2 protection for 8 h, and extracting, drying, and purifying to obtain a glycidyl methacrylate-isooctyl acrylate binary polymer;
[0062] S6: mixing 60 g of low-density polyethylene, 15 g of an ethylene-methyl acrylate copolymer, 17 g of a hyperbranched grafted modified coniferous wood fiber, 4 g of modified nano magnesium oxide, 10 g of a glycidyl methacrylate-isooctyl acrylate binary polymer, 1.5 g of di-tert-butyl peroxyisopropylbenzene, 1.5 g of 2,5-dimethyl-2,5-di(tert-butyl peroxy), 0.5 g of triallyl isocyanurate, and 0.5 g of trimethylolpropane triacrylate in a torque rheometer at 130°C to obtain a mixed sample, placing the mixed sample in a flat plate vulcanizing machine, hot pressing at 130°C and 15 MPa for 10 min, and crosslinking at 190°C and 15 MPa for 30 min to obtain an insulating layer material;
[0063] S7: after coating the copper core conductor with the insulating layer material, extruding a polyurethane protective sleeve on the outer layer to obtain a wind power cable.
[0064] Comparative Example 1:
[0065] S1: soaking 12 g of coniferous wood fiber in 30 mL of a 3-aminopropyl triethoxysilane aqueous solution with a mass fraction of 8% and a pH of 5 for 3 h, washing and drying to obtain silanized coniferous wood fiber;
[0066] S2: ultrasonic dispersion of 2 g of nano magnesium oxide powder in 10 mL of a 3- aminopropyl triethoxysilane isopropyl alcohol solution, the volume ratio of 3- aminopropyl triethoxysilane to isopropyl alcohol in the 3-aminopropyl triethoxysilane isopropyl alcohol solution being 1:10, stirring at 65°C for 10 h, and filtering and drying to obtain modified nano magnesium oxide;
[0067] S3: 2 g of glycidyl methacrylate and 6 g of isooctyl acrylate were mixed, 0.2 g of azobis isobutyronitrile and 0.8 g of n-dodecanethiol were added, and the mixture was reacted at 80°C under N2 protection for 7 h. After extraction, drying and purification, a glycidyl methacrylate-isooctyl acrylate binary polymer was obtained;
[0068] S4: 50 g of low-density polyethylene, 10 g of ethylene-methyl acrylate copolymer, 11.5 g of silanized coniferous wood fiber, 2 g of modified nano magnesium oxide, 6 g of glycidyl methacrylate-isooctyl acrylate binary polymer, 2 g of bis-tert-butyl peroxyisopropylbenzene, and 0.5 g of triallyl isocyanurate were mixed uniformly in a torque rheometer at 120°C to obtain a mixed sample. The mixed sample was placed in a flat plate vulcanizing machine and hot-pressed at 120°C and 15 MPa for 15 min, and then cross-linked at 180°C and 15 MPa for 40 min to obtain an insulating layer material;
[0069] S5: After the copper core conductor was coated with the insulating layer material, a polyurethane protective sleeve was extruded and coated on the outer layer to obtain a wind power cable.
[0070] Comparative Example 2:
[0071] In this comparative example, only the "hydroxyethyl acrylate" in step S3 was replaced with "the same amount of methyl acrylate", and the other steps and parameters were the same as in Example 1. The wind power cable was obtained as described in Example 1.
[0072] Comparative Example 3:
[0073] In this comparative example, step S4 was omitted, and only the "modified nano magnesium oxide" in step S6 was replaced with "the same amount of nano magnesium oxide", and the other steps and parameters were the same as in Example 1. The wind power cable was obtained as described in Example 1.
[0074] Comparative Example 4:
[0075] In this comparative example, step S5 was omitted, and only the "glycidyl methacrylate-isooctyl acrylate binary polymer" in step S6 was replaced with "the same amount of glycidyl methacrylate", and the other steps and parameters were the same as in Example 1. The wind power cable was obtained as described in Example 1.
[0076] Comparative Example 5:
[0077] In this comparative example, triallyl isocyanurate was not added during the preparation process of step S6, and the other steps and parameters were the same as in Example 1. The wind power cable was obtained as described in Example 1.
[0078] Performance Test:
[0079] The mechanical properties of the insulating layer materials prepared in Examples 1-3 and Comparative Examples 1-5 were tested using the national standard GB / T1040.2-2006. The mechanical properties of the insulating layer materials prepared in Examples 1-3 and Comparative Examples 1-5 were tested using a ball-plate electrode device at room temperature.
[0080] The DC breakdown strength of the insulating layer materials prepared in Examples 1-3 and Comparative Examples 1-5 was measured; a sample with a thickness of 100 μm was immersed in transformer oil to avoid surface flashover; a DC ramp voltage was applied at a rate of 500 V / s until breakdown occurred. Detailed results are shown in Table 1.
[0081] Table 1 Performance test of tensile strength, elongation at break and DC breakdown strength
[0082]
[0083] The insulating layer materials prepared in Examples 1-3 and Comparative Examples 1-5 were degassed in a vacuum oven at 80°C for 96 h, and then heat aged at 135°C for 30 days to test the tensile strength retention and elongation at break retention. ; The DC breakdown strength of the thermally aged insulation layer materials prepared in Examples 1-3 and Comparative Examples 1-5 was measured at room temperature using a ball-plate electrode device. Detailed results are shown in Table 2.
[0084] Table 2 Performance test of tensile strength retention, elongation at break and DC breakdown strength
[0085]
[0086] The wind power cables prepared in Examples 1-3 and Comparative Examples 1-5 were subjected to a torsion resistance test and a single cable burning test. The wind power cables were fixed on a torsion testing machine and tested at -40°C and 50°C, respectively. The torsion mode was horizontal 2D torsion, the torsion angle was ±180°, the torsion speed was 12 times / min, and the number of torsion cycles that the cable could withstand before breaking was recorded. The single cable burning test was conducted in accordance with IEC 60811-1-4, as shown in Table 3 for details.
[0087] Table 3 Performance test of twist resistance, single cable burning length and cable self-extinguishing time
[0088]
[0089] Data Analysis:
[0090] It can be seen from Table 1, Table 2 and Table 3 that the wind power generation cable prepared by the present invention has excellent mechanical properties, DC breakdown resistance, flame retardancy and aging resistance.
[0091] Compared with the embodiment, the mechanical properties and anti-aging ability of the wind power cable prepared in Comparative Example 1 are significantly reduced, because the silanized coniferous wood fibers are not grafted and modified by hyperbranched polyamides, and a large number of active amino groups and hydroxyl groups are not introduced, thereby reducing the interfacial bonding force between the fibers and other materials and losing the heat shielding and anti-thermal oxidative degradation ability provided by the hyperbranched structure.
[0092] Compared with the embodiment, the mechanical properties and anti-aging ability of the wind power cable prepared in Comparative Example 1 are significantly reduced, because the silanized coniferous wood fibers are not grafted and modified by hyperbranched polyamides, and a large number of active amino groups and hydroxyl groups are not introduced, thereby reducing the interfacial bonding force between the fibers and other materials and losing the heat shielding and anti-thermal oxidative degradation ability provided by the hyperbranched structure.
[0093] In Comparative Example 3, the nano magnesium oxide is not surface-modified, and the amino and siloxane functional groups are not introduced on the surface of the nano magnesium oxide, thereby reducing the dispersibility and interfacial effect of the magnesium oxide. In addition, the amino and siloxane functional groups on the surface of the modified nano magnesium oxide can act as deep trap centers to effectively capture carriers, thereby inhibiting the accumulation of space charges. The accumulation of space charges can cause electric field distortion, accelerate the aging and breakdown of the material, and the modified nano magnesium oxide improves the electrical insulation performance of the insulating material by inhibiting the accumulation of space charges.
[0094] In Comparative Example 4, the “glycidyl methacrylate-isooctyl acrylate binary polymer” is replaced by “glycidyl methacrylate of the same mass”. The isooctyl acrylate in the glycidyl methacrylate-isooctyl acrylate binary polymer introduces alkyl side chains with a longer length, which provides more free volume and segment motion ability in the polymer chain, thereby improving the flexibility and impact resistance of the copolymer. The optimization of this structure enables the composite material to better disperse stress and reduce material fatigue accumulation under repeated twisting and mechanical stress, thereby improving its twisting resistance. Therefore, the twisting resistance of Comparative Example 4 is reduced compared with the embodiment.
[0095] In Comparative Example 5, the organic compound triallyl isocyanurate with multiple double bond functional groups is not added. The half-life temperature of the peroxide and the crosslinking agent is similar to the processing temperature of polyethylene, resulting in a narrow processing window for crosslinked polyethylene. The organic compound triallyl isocyanurate with multiple double bond functional groups can rapidly react with the generated polyethylene macromolecular chain radicals after the peroxide decomposes to generate radicals and undergoes a hydrogen abstraction reaction on the polyethylene molecular chain, and the generated polymer radicals are stable. Therefore, the crosslinking efficiency can be improved, and the amount of peroxide can be reduced.
[0096] Those skilled in the art should understand that the above discussion of any embodiment is merely exemplary in nature and is not intended to imply that the present application is limited to these examples; any of the above embodiments or technical features among different embodiments can be combined, and steps can be implemented in any order, under the idea of the present application, and there are many other changes of different aspects of the present application as described above, which are not provided in details for the sake of brevity.
[0097] The present application is intended to cover all such alternatives, modifications, and variations as come within the scope of the broadest possible interpretation of the appended claims. Accordingly, any and all such alternations, modifications, equivalents, improvements and the like are intended to be encompassed by the present application.
Claims
1. A wind power generation cable, comprising a conductor, an insulating layer, and a protective sheath arranged in sequence from the inside to the outside, characterized in that: The insulating layer material is made of the following raw materials in parts by mass: 50-60 parts of low-density polyethylene, 10-15 parts of ethylene-methyl acrylate copolymer, 11.5-17 parts of hyperbranched grafted modified softwood fiber, 2-4 parts of modified nano magnesium oxide, 6-8 parts of a crosslinking agent, 2-3 parts of a peroxide, and 0.5-1 part of a crosslinking agent auxiliary.
2. The wind power generation cable according to claim 1, characterized in that: Preparation method of the hyperbranched grafted modified softwood fiber: Step A1: soaking softwood fiber in an aqueous solution of 3-aminopropyltriethoxysilane for 3-5 hours, washing, and drying to obtain silanized softwood fiber; dispersing the silanized softwood fiber in anhydrous methanol a1; adding methyl acrylate a and triethylamine a; reacting at 60°C-65°C under nitrogen protection for 5-6 hours; washing and drying; and adding anhydrous methanol a2 and ethylenediamine a; reacting at 55°C-60°C under nitrogen protection for 7-8 hours to obtain modified softwood fiber A; Step A2: Dispersing modified softwood fiber A in anhydrous methanol b1, adding methyl acrylate b and triethylamine b, reacting at 65°C-70°C under nitrogen protection for 5-6 hours, washing and drying, adding anhydrous methanol b2 and ethylenediamine b, reacting at 55°C-60°C under nitrogen protection for 7-8 hours to obtain modified softwood fiber B; Step A3: Disperse the modified coniferous wood fiber B in anhydrous methanol c1, add hydroxyethyl acrylate and triethylamine c, react at 65°C-70°C under N2 protection for 5-6 hours, wash and dry, add anhydrous methanol c2 and ethylenediamine c, react at 55°C-60°C under N2 protection for 7-8 hours to obtain hyperbranched grafted modified coniferous wood fiber.
3. The wind power generation cable according to claim 2, characterized in that: The mass ratio of the softwood fiber, 3-aminopropyltriethoxysilane aqueous solution, methyl acrylate a, methyl acrylate b, hydroxyethyl acrylate, triethylamine a, triethylamine b, triethylamine c, ethylenediamine a, ethylenediamine b, and ethylenediamine c is 10:60-80: 0.85-1.3:1.7-2.6:3.5-5.5:1.05-1.4:2.1-2.8:4.2-5.6:0.6-1.05:1.2-2.1:2.4-4.2。 4. The wind power generation cable according to claim 2, characterized in that: The mass fraction of the 3-aminopropyltriethoxysilane aqueous solution is 8%-10%, and the pH value of the 3-aminopropyltriethoxysilane aqueous solution is 5-6.
5. The wind power generation cable according to claim 1, characterized in that: The preparation method of the modified nano-magnesium oxide comprises the following steps: ultrasonically dispersing nano-magnesium oxide powder in a 3-aminopropyltriethoxysilane isopropanol solution, stirring at 65° C.-75° C. for 8-10 hours, filtering, and drying to obtain the modified nano-magnesium oxide.
6. The wind power generation cable according to claim 1, characterized in that: The preparation method of the crosslinking agent comprises the following steps: mixing glycidyl methacrylate and isooctyl acrylate, adding azobisisobutyronitrile and n-dodecyl mercaptan, reacting at 80-90° C. under N2 protection for 7-8 hours, extracting, drying, and purifying to obtain a glycidyl methacrylate-isooctyl acrylate binary polymer, namely the crosslinking agent.
7. The wind power generation cable according to claim 1, characterized in that: The peroxide is any one or two of di-tert-butylperoxyisopropylbenzene and 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane.
8. The wind power generation cable according to claim 1, characterized in that: The crosslinking auxiliary agent is any one or two of triallyl isocyanurate and trimethylolpropane triacrylate.
9. The wind power generation cable according to claim 1, characterized in that: The preparation method of the insulating layer material comprises the following steps: uniformly mixing low-density polyethylene, ethylene-methyl acrylate copolymer, hyperbranched grafted modified softwood fiber, modified nano magnesium oxide, a crosslinking agent, a crosslinking agent auxiliary and an antioxidant in a torque rheometer at 120° C.-130° C. to obtain a mixed sample; placing the mixed sample in a flat vulcanizer at 120° C.-130° C. and 15 MPa for hot pressing for 10-15 minutes; heating the mixture to 180° C.-190° C. and crosslinking the mixture at 15 MPa for 30-40 minutes to obtain the insulating layer material.
10. A method for preparing a wind power cable according to any one of claims 1 to 9, characterized in that: A high-performance wind power generation cable is produced by sequentially coating the outer surface of a conductor with an insulating layer and a protective sheath.
Citation Information
Patent Citations
Method for improving mechanical performance of composite material by grafting hyperbranched polyamide on plant fiber surface
CN104448567A
Thin-wall sheath cable and rapid forming process thereof
CN119207869A